2015
DOI: 10.1371/journal.pone.0115329
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Restriction during Simulated Wildfire Suppression: Effect on Physical Task Performance

Abstract: ObjectivesTo examine the effects of sleep restriction on firefighters’ physical task performance during simulated wildfire suppression.MethodsThirty-five firefighters were matched and randomly allocated to either a control condition (8-hour sleep opportunity, n = 18) or a sleep restricted condition (4-hour sleep opportunity, n = 17). Performance on physical work tasks was evaluated across three days. In addition, heart rate, core temperature, and worker activity were measured continuously. Rate of perceived an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 48 publications
1
49
1
Order By: Relevance
“…A total of 12 participants wore the ActiSleep monitor on 152 nights throughout the 2014 fire season, and average TST regardless of deployment type was found to be 364 ± 61.2min/night (~6 ± 1hrs/night). This finding is consistent with the TST observed in Australian Rangers during deployments [55,56]. Accordingly, 6hrs/night was used for daily energy expenditure estimation by multiplying this value by the corresponding Compendium of Physical Activities value for sleeping (1.0METs) [54].…”
Section: Methodssupporting
confidence: 72%
See 1 more Smart Citation
“…A total of 12 participants wore the ActiSleep monitor on 152 nights throughout the 2014 fire season, and average TST regardless of deployment type was found to be 364 ± 61.2min/night (~6 ± 1hrs/night). This finding is consistent with the TST observed in Australian Rangers during deployments [55,56]. Accordingly, 6hrs/night was used for daily energy expenditure estimation by multiplying this value by the corresponding Compendium of Physical Activities value for sleeping (1.0METs) [54].…”
Section: Methodssupporting
confidence: 72%
“…While FireRangers are still required to perform physical labour while working at the base, in preparation for fire deployments, our findings indicate that these workers have an opportunity to rest and recover from the intense physical demands of fire suppression activities while they await subsequent fire deployments. Other research on Australian FireRangers has indicated that they are able to self-regulate their daily physical activity in order to maintain task performance and subjective measures of exertion over consecutive days performing fire suppression tasks [56,67]. This research indicates that FireRangers exhibit “activity synergy”.…”
Section: Discussionmentioning
confidence: 89%
“…Indeed, in a highly competitive team weight-lifting environment, Blumert et al [100] found that maximal strength is not impaired by 24 h of complete sleep deprivation. We have also shown that firefighters working in teams will maintain their physical performance on important tasks without a decrease in motivation or perceived exertion [101]. Neither of these acute sleep restriction or deprivation environments are a true proxy for the chronic sleep disruptions commonplace for shiftworkers.…”
Section: Potential Countermeasures To Preserve Skeletal Muscle Heamentioning
confidence: 99%
“…The physical work circuit comprised six simulated wildland firefighting tasks designed to mimic the physical demands involved in Australian wildfire suppression work (Ferguson et al 2011;Phillips et al 2012;Vincent et al 2015). A job task analysis was used to design the firefighting work circuit.…”
Section: Simulated Physical Firefighting Work Circuitmentioning
confidence: 99%
“…The tasks included lateral repositioning of a hose, rake hoe work, hose rolling, charged hose advance, black out hose work, and static hold of a hose. The performance of each physical task (i.e., repetitions completed for each task within each work period) was self-paced and completed in a predetermined order with work-to-rest ratios designed to mimic the performance of these tasks on the fire-ground (Ferguson et al 2011;Phillips et al 2015;Vincent et al 2015).…”
Section: Simulated Physical Firefighting Work Circuitmentioning
confidence: 99%